Pilates in sport dance training - Ljubojevic, A.; Gerdijan, N.; Sebic, L.; Karalic, T. (Sports Science and Health, 2018)
The aim of this paper is to point out the many advantages of using the Pilates method of exercise in comprehensive preparations of dancers. Using Pilates as a training model in sport dance, largely ensures easier movement performance technique, more effective dance couple movement, provides better dance expression, prevents injuries and ensures the longevity of a dancer`s career. Introducing dancers to intellectual and kinesthetic relations between dance and Pilates also promotes the achievement of goals such as the increased body awareness, improved musculoskeletal integration, and in general, provide better health for dancers. Diversity of various Pilates instruments does not make exercise monotonous and allows for a progressive effect on mobility and stability of all dance performances.